Human milk oligosaccharides, milk microbiome and infant gut microbiome modulate neonatal rotavirus infection. Issue 1 (December 2018) - Ramani, Sasirekha; Stewart, Christopher; Laucirica, Daniel; Ajami, Nadim; Robertson, Bianca; Autran, Chloe; Shinge, Dhairyasheel; Rani, Sandya; Anandan, Sasirekha; Hu, Liya; Ferreon, Josephine; Kuruvilla, Kurien; et al.
Abstract Neonatal rotavirus infections are predominantly asymptomatic. While an association with gastrointestinal symptoms has been described in some settings, factors influencing differences in clinical presentation are not well understood. Using multidisciplinary approaches, we show that a complex interplay between human milk oligosaccharides (HMOs), milk microbiome, and infant gut microbiome impacts neonatal rotavirus infections. Validating in vitro studies where HMOs are not decoy receptors for neonatal strain G10P[11], population studies show significantly higher levels of Lacto-N-tetraose (LNT), 2'-fucosyllactose (2'FL), and 6'-siallylactose (6'SL) in milk from mothers of rotavirus-positive neonates with gastrointestinal symptoms. Further, these HMOs correlate with abundance ofEnterobacter /Klebsiella in maternal milk and infant stool. Specific HMOs also improve the infectivity of a neonatal strain-derived rotavirus vaccine. This study provides molecular and translational insight into host factors influencing neonatal rotavirus infections and identifies maternal components that could promote the performance of live, attenuated rotavirus vaccines. Neonatal rotavirus infections are associated with gastrointestinal symptoms in some settings, but the role of host factors in clinical presentation is unclear. Here, Ramani et al. show that human milk oligosaccharides and microbiome are associated with symptomatic infection with neonatal strain G10P[11].